2001
DOI: 10.1246/bcsj.74.123
|View full text |Cite
|
Sign up to set email alerts
|

Platinum-Catalyzed Bis-Germylation of Alkynes with Organodigermanes and Cyclic Oligogermanes

Abstract: Hexamethyldigermane, Me3GeGeMe3, reacted with various alkynes in the presence of platinum complexes at 120 °C to afford Z–1,2-bis(germyl)ethenes in moderate to good yields. Terminal alkynes exhibit higher reactivities than internal ones. [Pt(acac)2] and [Pt(dba)2] serve as efficient catalysts, while [Pt(PPh3)4], [PtCl2(PPh3)2], and [Pt(dba)2]-phosphite were found to be inactive. Four- and six-membered cyclic oligogermanes, such as dodecamethylcyclohexagermane, (Me2Ge)6, reacted with alkynes in the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 25 publications
0
33
0
Order By: Relevance
“…Then, Z-a,bbis(chlorodiethylgermyl)styrene (1b) was purified simply by distillation (Kugelrohr) under reduced pressure to give 1b (7.71 g, 0.20 mol, 43%). 1b: bp 80-140°C/0.02 mmHg; 1 H NMR (d, CDCl 3 ) 1.09 (m, 10H, EtGe), 1.25 (m, 10H, EtGe), 6.90 (s, 1H, CH@), 7.10-7.42 (m, 5H, phenyl ring protons); 13 C NMR (d,CDCl 3 ) 8.19,8.72,12.99,15.94,126.06,127.36,128.55,144.62,148.15,158.84. MS m/z (relative intensity): 405 (88), 370 (11), 341 (10), 268 (33), 239 (30), 166 (100).…”
Section: Preparation Of Z-ab-bis(chlorodiethylgermyl)-styrene (1b)mentioning
confidence: 99%
See 3 more Smart Citations
“…Then, Z-a,bbis(chlorodiethylgermyl)styrene (1b) was purified simply by distillation (Kugelrohr) under reduced pressure to give 1b (7.71 g, 0.20 mol, 43%). 1b: bp 80-140°C/0.02 mmHg; 1 H NMR (d, CDCl 3 ) 1.09 (m, 10H, EtGe), 1.25 (m, 10H, EtGe), 6.90 (s, 1H, CH@), 7.10-7.42 (m, 5H, phenyl ring protons); 13 C NMR (d,CDCl 3 ) 8.19,8.72,12.99,15.94,126.06,127.36,128.55,144.62,148.15,158.84. MS m/z (relative intensity): 405 (88), 370 (11), 341 (10), 268 (33), 239 (30), 166 (100).…”
Section: Preparation Of Z-ab-bis(chlorodiethylgermyl)-styrene (1b)mentioning
confidence: 99%
“…Za,b-bis(chlorodiisopropylgermyl)styrene (1c) was purified simply by distillation (Kugelrohr) under reduced pressure in 1. Hz, 2H, CH), 6.89 (s,1H,CH@),5H,Ph); 13 C NMR (d,CDCl 3 ) 18.36,18.72,19.20,19.53,21.62,24.69,126.35,127.31,128.51,145.52,149.68,158.05. MS m/z (relative intensity): 490 (M + , 13), 447 (100), 404 (26).…”
Section: Preparation Of Z-ab-bis(chlorodiisopropyllgermyl)-styrene (1c)mentioning
confidence: 99%
See 2 more Smart Citations
“…The conformational energy barrier for the ring inversion of 1,3,6-cyclooctatriene was calculated to be only 4.1 kcal/mol above the ground state. On the other hand, the 1 H and 13 C NMR spectra of the eight-membered disilacarbocycles, 1,1,4,4-tetramethyl-5,6, 7,8-tetraphenyl-1,4-disilacycloocta-2,5,7-triene derivatives 2,3 having phenyl substituents on the ring and 1,1,6,6-tetramethyl-1,6-dihydrotribenzo-[b,e,g][1,4]-disilocine 4 having a biarylene moiety such as a biphenylene, indicated that the two methyl groups on the silicon atom of these eightmembered disilacarbocycles were nonequivalent. This nonequivalence of the two methyl groups on the silicon atom in the compounds may be due to the steric repulsions between the methyl substituents on the silicon atom and the phenyl substitutents or biphenylene moiety of the eight-membered ring.…”
Section: Introductionmentioning
confidence: 99%